The person with heart failure in the perspective of finitude: an understanding in the light of Martin Heidegger - Lorena Campos de Souza; Amanda Caboclo Flor; Thiago Martins de Sousa; Luigina Mortari; Virna Ribeiro Feitosa Cestari; Marina de Góes Salvetti; Vera Lúcia Mendes de Paula Pessoa (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To understand the experience of finitude from people with advanced-stage heart failure. Method: Phenomenological study conducted in a tertiary referral hospital in cardiology, in Fortaleza - CE, from August to October 2022. The participants were 11 patients with advanced-stage heart failure. Data collection was conducted through semi-structured interviews, and the speeches were recorded and transcribed for analysis using Heideggerian hermeneutic circle. Results: Of the 11 participants, eight were men; ages ranged from 43 to 82 years. The results were processed through the hermeneutic reduction process, which allowed the construction of two categories: (1) Being-with the other in heart illness and finitude, consisting of meanings related to the patients’ physical conditions, their limitations and possibilities, and their interpersonal relationships, (2) The construction of being-toward-death, in which patients spoke about their fears, anxieties, perceptions, and concerns in the face of finitude. Final considerations: The person with heart failure in the perspective of finitude experiences a phenomenon marked by the lack of information about the severity of the disease and the proximity of the end, which hinders the communication of their needs and conscious choices, resulting in an inauthentic existence.